Medication Safety in Polypharmacy - (:unkn) unknown (World Health Organisation, 2019)
Ensuring medication safety in polypharmacy is one of the key challenges for medication safety today. Due to the traditional focus of both medical research and health care delivery models on single-disease interventions, there has been a notable lack of evidence-based solutions. Conventionally polypharmacy has been perceived as an overuse of medicines, whereas it may be more useful to perceive in terms of appropriateness,as there are many cases where the concurrent use of multiple medicines may be deemed necessary and beneficial. Globally the prevalence of polypharmacy is set to rise as the population ages and more people suffer from multiple long-term conditions. Countries should therefore prioritize raising awareness of the problems associated with inappropriate polypharmacy and the need to address this issue. All stakeholders have a vital role to play in driving change for the management of polypharmacy. Polypharmacy management involves multifaceted decision-making and necessitates the combined knowledge of physicians, nurses, pharmacists and other health care professionals, including the systematic involvement, engagement and empowerment of patients. Thus it is important to implement interventions, such as medication reviews, whenever possible in collaboration with the patient and/or the caregiver. Good communication and accurate sharing of information is essential and can be facilitated by the use of patient-held medication records.Furthermore, a redesign of care processes
Keywords: Inclusive Society; Medication safety; POLYPHARMACY; Patient safety